Pedogenesis of high-mountain soils from Serra da Mantiqueira, Brazil - Cipriano da Silva, Rafael (Revista Ciência Agronômica, 2021)
In the Serra da Mantiqueira region the pedogenetic studies contribute to both the understanding of past eventsand supporting the conservation of natural resources. This study aimed to characterize the soils from the Minas Gerais highmountains region to evaluate the influence of paleoenvironmental conditions on pedogenesis. Five profiles were selected andcharacterized for morphological, physical and chemical properties. Isotopic analyses of 13C were performed in soil samplescollected at depths of 10, 20, 30, 40, 50, 60, 80 and 100 cm; except in P2, which was collected up to 60 cm deep. Erraticdistribution of the particle-size fractions and C contents highlight the sedimentary nature of the profiles, resulting from theerosive action favored by the relief. High organic C content in subsurface and its accumulation in the surface were observedin the profi les, which suggests the occurrence of the melanization process. In the profi les P2, P4 and P5 (Cambissolos/ Cambisols)the brownish color indicates the xanthization process, while in P1 (Argissolo/ Lixisol), is highlighted the process of eluviationand illuviation resulting in the increase of clay in subsurface and presence of clay films. In P3 (Latossolo/ Ferralsol), the lowvalues of sum of bases, silica removal and SiO2/Al2O3ratio (ki index) values below 1.0 point to the advanced weathering andthe allitization process. The variation in the isotopic signature of δ13C indicates a drier past condition, with mixed vegetation, withgradual change of vegetation with predominant C3photosynthetic pathway. In P1 and P4, the decrease in the contents of δ13C insurface results from anthropic action.